A type I hybrid ARQ system with adaptive code rates - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 1995)
Type I hybrid ARQ systems use an error-control code of fixed rate for error-correction in each transmitted packet. In such systems, the code rate must be carefully chosen to match the channel bit error rate (BER) in order to maximize system throughput. Whenever there is a mismatch between code rate and channel BER, the throughput suffers. In this paper, we proposed a type I hybrid ARQ system which automatically adjusts its code rates to match channel BERs. The proposed system is very simple to implement and yet performs significantly better than type I hybrid ARQ systems of fixed code rate